Periodic Lagrangian Coherent Structures around a tidal inlet - De Leo, Annalisa; Enrile, Francesco; Stocchino, Alessandro (Frontiers in Marine Science, 2022)
We present an extensive experimental campaign dedicated to the identification of coherent trajectory patterns owing to flow occurring in tidal environments, characterized by a tidal inlet and a channel with lateral tidal flats. Single and multiple harmonics tides are here reproduced on a large-scale physical model. The study of the large scale macro-vortices, generated by vortex shedding during the flood phase from the inlet barrier, is performed employing the Lagrangian Average Vorticity Deviation (LAVD). The presence of large-scale vortices with a complex dynamics within a tidal period suggested a deeper understanding on the possible environmental implications in terms of transport connections or barriers. Finite Time Lyapunov Exponents are employed in order to recognize stable and unstable manifolds within the flow that are defined as preferred paths along which particles are repelled (forward integration) or attracted (backward).